O papel do outro na atuação do professor coordenador - Pessôa, Lilian Corrêia (2010)
Supposing that the other exerts relevant influence at a professional actuation, this search looks for to understand the figure that this other exerts on a Coordinator Teaching actuation. From this point of view, we believe to be possible to catch relevant aspects which may contribute for an improvingly better actuation of this professional with his teaching staff altogether. The methodology adopted to compose this search was an autobiographic narrative since we understand that the analysis of a particular trajectory may disclose aspects of that category as a whole. Thereby we selected a coordinator Teacher, whose work has been considered outstanding during all the time he exerted that function, as expressed by those who had worked with him. The psychogenetic theory of Henry Wallon, more specifically the section referring to the me-other relationship, means and integration (of functional dimensions, affectivity, motion act, knowledge and person, as well as organismmean), was the reason for the question of this search, and offered resources to illuminate the analysis data. As a result of the proposed analysis, some points excelled: the relationship me-other, implies changes, reciprocity; the relationship meother based on negotiations propitiates more favorable conditions to the development; the intimate other, constant partner of me, turns apparent at decisions situations and course changes. To understand the person at an integrator perspective, permits re-evaluate the Coordinator Teacher pedagogic practices together with his teaching staff, turning it to a more adequate to the teaching-learning process development